HYBRID COLLABORATIVE BUSINESS MODEL: THE MISSING LINK BETWEEN AMBIDEXTERITY AND STRATEGIC BUSINESS PERFORMANCE FOR SMES - Noor Hasvenda Abd Rahim; Hasliza Abdul Halim (International Journal of Accounting, Finance and Business, 2023)
This study examines the relationship between organisational ambidexterity, hybrid collaborative business models, and strategic performance in Malaysian SMEs from the lens of the Extended Resource Based View theory. Drawing on interdisciplinary sources, a conceptual framework was developed to explore the determinants of SMEs strategic performance viewed from the standpoint of ambidexterity and collaborative business models. The study finds that organisational ambidexterity is a crucial factor in SMEs strategic performance, and hybrid collaborative business model design can act as a mediator in this relationship. The study offers practical implications for SME owners and managers to understand the importance of ambidexterity and collaborative business models in improving strategic performance. The conceptual framework presented can serve as a foundation for future empirical studies and offers variables that strengthen strategic performance. This study is unique in its exploration of the interplay between internal strategic resources and external influences on the strategic performance of SMEs in Malaysia. By shedding light on this relationship, the study offers valuable insights into how SMEs can navigate the complexities of today's business environment and sustain their impact through collaborative measures.